Liver transplantation for hereditary tyrosinemia: the Quebec experience. - Paradis, K (1990)
Sixteen tyrosinemic patients were evaluated in our institution for a possible liver transplantation. All patients showed biochemical and/or radiological evidence of liver dysfunction. Renal involvement was found to be more abnormal than expected. Seven patients have been transplanted, with two patients receiving a combined liver-kidney transplant. Hepatocarcinoma was detected in two of eight patients in whom the whole liver was examined. Six (37.5%) of the initial 16 patients have died since evaluation, one of the six dying after combined liver-kidney transplantation. Posttransplantation survival was 86%, with normal liver function, normal growth, and no recurrence of neurological crises on a normal diet.